(untitled) (Journal of Biomedical Investigation, 2025)
Background: Lower limb amputees usually have reduced mobility which affects their capacity to carry out daily tasks and physical activity which greatly affects their quality of life (QoL). Aim: This study determined the QoL, physical activity and their associations with demographic and clinical factors of lower limb amputees at University of Maiduguri Teaching Hospital. Methods: This was a cross-sectional survey involving fifty amputees recruited through a convenience sampling technique. Quality of life was assessed using the WHOQOL-Bref (Hausa version) while physical activity (PA) was assessed using the International Physical Activity Questionnaire (IPAQ)- short form (Hausa version). Socio-demographic information of age, gender, level of education, and clinical factors such as cause of amputation, level of amputation and time since amputation were also obtained. Data were analysed by descriptive statistics and inferential statistics of Chi-square (ꭓ2 ) test. Statistical significance was set at p<0.05. Results: Quality of life was higher in the “psychological” domain (67.88±13.52), relatively lower in the “social” domain of QoL (59.00±17.30). It shows (30%) low physical activity (570.24±555.69 MET min/week), a high percentage (56%) of moderate physical activity level (649.60±884.61 MET-min/week) and (14%) vigorous physical activity (685.60±1868.24 MET-min/week) among the amputees. Significant associations between physical domain and age (p<0.05), psychological domain and level of education (p<0.05), environmental domain and cause of amputation (p<0.05). No significant associations (p>0.05) were found between the QoL domains with either gender, level of amputation and time since amputation. There was a significant association between physical activity levels with age and time including amputation (p<0.05) respectively. Conclusion: There was a moderate physical activity level among lower limb amputees, with quality of life higher in the psychological domain which significantly associated with age, level of education and cause of amputation. Benefits of physical activity to the amputees at both the preoperative and postoperative phases of rehabilitation should be disseminated by healthcare professionals to enhance overall quality of lining.